Safety of Current Therapies for Cardiogenic Cerebral Embolism: A Systematic Review - Motaharnia , Arefeh; Khorsand, Kamyar; Haratian, Negar; Masoumi, Samira; Alipour, Maryam; Hemmati, Sara; Rostami Ghezeljeh, Mahsa; Akhbari, Matin; Karami , Shaghayegh; Azhdarimoghaddam , Aida; et al. (Journal of Endovascular Resuscitation and Trauma Management, 2025)
Background: Cardiogenic cerebral embolism (CCE) accounts for approximately 20% of ischemic strokes and presents with severe neurological deficits and high mortality rates. The safety and effectiveness of current therapeutic strategies remain under evaluation. This systematic review aims to assess the safety profiles of current therapies, including thrombolysis, endovascular thrombectomy, anticoagulants, and antiplatelets, in patients with CCE. Methods: A systematic search was conducted in Web of Science, Scopus, and PubMed for studies published up to May 2024. Articles were screened using the Rayyan intelligence tool, and their quality was assessed using the JBI critical appraisal tool. The review included randomized controlled trials (RCTs) and observational studies evaluating the safety and outcomes of different CCE treatment modalities. Results: Ten studies met the inclusion criteria. Endovascular thrombectomy demonstrated improved functional outcomes with a reduced risk of mortality, although symptomatic intracranial hemorrhage (sICH) rates were comparable to other therapies. Intravenous thrombolysis with alteplase was associated with increased sICH risk but reduced 90-day mortality. Direct oral anticoagulants (DOACs), including apixaban and edoxaban, showed a favorable safety profile with no significant increase in intracranial bleeding. Antiplatelet therapy, particularly low-dose tirofiban, demonstrated reduced in-hospital mortality without increasing hemorrhagic risk. Conclusion: While current therapies for CCE improve outcomes, their safety profiles vary. Endovascular thrombectomy appears effective for severe cases, whereas DOACs provide a safe alternative for long-term anticoagulation. Further large-scale trials are needed to refine treatment guidelines and minimize hemorrhagic risks.